Hfqs in Bacillus anthracis: Role of protein sequence variation in the structure and function of proteins in the Hfq family. (30th August 2015) - Vrentas, Catherine; Ghirlando, Rodolfo; Keefer, Andrea; Hu, Zonglin; Tomczak, Aurelie; Gittis, Apostolos G.; Murthi, Athulaprabha; Garboczi, David N.; Gottesman, Susan; Leppla, Stephen H.
Abstract Hfq proteins in Gram‐negative bacteria play important roles in bacterial physiology and virulence, mediated by binding of the Hfq hexamer to small RNAs and/or mRNAs to post‐transcriptionally regulate gene expression. However, the physiological role of Hfqs in Gram‐positive bacteria is less clear. Bacillus anthracis, the causative agent of anthrax, uniquely expresses three distinct Hfq proteins, two from the chromosome (Hfq1, Hfq2) and one from its pXO1 virulence plasmid (Hfq3). The protein sequences of Hfq1 and 3 are evolutionarily distinct from those of Hfq2 and of Hfqs found in other Bacilli. Here, the quaternary structure of each B. anthracis Hfq protein, as produced heterologously in Escherichia coli, was characterized. While Hfq2 adopts the expected hexamer structure, Hfq1 does not form similarly stable hexamers in vitro. The impact on the monomer–hexamer equilibrium of varying Hfq C‐terminal tail length and other sequence differences among the Hfqs was examined, and a sequence region of the Hfq proteins that was involved in hexamer formation was identified. It was found that, in addition to the distinct higher‐order structures of the Hfq homologs, they give rise to different phenotypes. Hfq1 has a disruptive effect on the function of E. coli Hfq in vivo, while Hfq3 expression at high levels is toxic to E. coli but also partially complements Hfq function in E. coli. These results set the stage for future studies of the roles of these proteins in B. anthracis physiology and for the identification of sequence determinants of phenotypic complementation.